BASIC GLOBAL RESEARCH TRENDS ON CADASTRE: A BIBLIOMETRIC ANALYSIS (2002-2012) - Erkinova M.L (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract  In this article, particularly the global research status of cadastre was evaluated by using bibliometric analysis. This article is based on the analysis of research topics, scientific production, collaboration among countries and authors. Furthermore, most cited papers on cadastre research which obtained from database of Scopus during the time period from 2012 to 2023. Land use changes, as a practical and advanced space exploration technology, offered a lot of valuable data about the earth surface for global analysis.  This  study  is  concentrated  on  the  analysis  of  scientific  outputs,  research directions, source journals, author performance and their contribution, the distribution of  research  countries/territories  as  well  as  institutions  and  their  collaboration  and temporal trends in keywords usage.